Concurrent validity and between-unit reliability of a foot-mounted inertial measurement unit to measure velocity during team sport activity - Myhill, N.; Weaving, D.; Robinson, M.; Barrett, S.; Emmonds, S. (Science and Medicine in Football, 2024)
The concurrent validity and between-unit reliability of a foot-mounted inertial measurement unit (F-IMU) was investigated during linear and change of direction running drills. Sixteen individuals performed four repetitions of two drills (maximal acceleration and flying 10 m sprint) and five repetitions of a multi-directional movement protocol. Participants wore two F-IMUs (Playermaker) and 10 retro-reflective markers to allow for comparisons to the criterion system (Qualisys). Validity of the F-IMU derived velocity was assessed via root-mean-square error (RMSE), 95% limits of agreement (LoA) and mean difference with 95% confidence interval (CI). Between-unit reliability was assessed via intraclass correlation (ICC) with 90% CI and 95% LoA. The mean difference for instantaneous velocity for all participants and drills combined was -0.048 ± 0.581 m · s-1, the LoA were from -1.09 to -1.186 m · s-1 and RMSE was 0.583 m · s-1. The ICC ranged from 0.84 to 1, with LoA from -7.412 to 2.924 m · s-1. Differences were dependent on the reference speed, with the greatest absolute difference (-0.66 m · s-1) found at velocities above 7 m · s-1. Between-unit reliability of the F-IMU ranges from good to excellent for all locomotor characteristics. Playermaker has good agreement with 3D motion capture for velocity and good to excellent between-unit reliability.